Meat sector and its development - Kondaiah, N; Pragati, H (The Indian Journal of Animal Sciences, 2005)
Optimum utilization of meat animal resources through developlment of meat sector is important not only to provide meat and by products of human utility but also to sustain livestock production ensuring better returns to farmers. Improvement of slaughter houses for clean meat production and to provide a positive image to meat sector. is a social priority as it is associated with food safety and security besides religious implications. R and D efforts need to promote entrepneurial activity) which in turn would contribute for organized development of meat sector. Development of value added meat products utilizing tough meat, byproducts, non-meat ingridients with Indian spices, condiments and culinary practices would result in processed meat sector development, which is a priority in the post WTO period to sustain Indian meat sector prospects. Relevant quality conlrol approaches and low cost waste disposal means are essential. Meat sector development could be and important activity in the diversification of agriculture.